Neutrophil To Lymphocyte Ratio as A Marker of COVID-19 Disease Severity in Banda Aceh - Devi Efrina; Herry Priyanto; Novita Andayani; Yunita Arliny; Budi Yanti (Jurnal Respirologi Indonesia, 2021)
Background: Patients with severe COVID-19 always coincide with high mortality rate, meanwhile, inflammatory immunity parameters in COVID-19 infection such as Neutrophil to Lymphocyte Ratio (NLR) reflect the infection progress. These are used by clinicians for early identification of patients at high risk or to determine when it is a serious disease. This study aims to determine the effectiveness of NLR as a marker of COVID-19 pneumonia severity.Method: This study was conducted using a retrospective cross-sectional analytical design at the Regional General Hospital of DR. Zainoel Abidin Banda Aceh from June to September 2020. Patients' demographic characteristics, comorbidities, clinical manifestations of COVID-19 infection, chest x rays, examination of blood samples at admissions such as leukocytes, lymphocytes, neutrophils and NLR were extracted from medical record data. The patients were divided into four groups according to the disease severity, namely mild, moderate, severe and critical.Result: A total of 105 medical records were collected for COVID19 patients, meanwhile, 51 to 70 years was the largest age group (60.8%) with twice male than female. Moreover, fever, cough, shortness of breath and weakness are the most common symptoms found in treated patients while almost two-thirds of the patients have bilateral pneumonia. Generally, the levels of leukocytes, neutrophils, NLR were found to increase while the levels of lymphocytes decreased, in addition, more than half of the COVID19 patients were severe. There was a strong relationship between an increase in NLR levels and COVID-19 disease severity (95% CI, α: 0.05, p = 0.001)Conclusion: Based on the results, NLR is applicable as an early inflammatory marker which reflects severe and critical COVID19 infection and also suitable as an objective basis for early identification and management of severe COVID-19 pneumonia.